Effectiveness and Safety of Percutaneous Thrombectomy Devices: Comparison of Rotarex and Angiojet in a Physiological Circulation Model. (June 2020) - Rusch, René; Trentmann, Jens; Hummitzsch, Lars; Rusch, Melanie; Aludin, Schekeb; Haneya, Assad; Albrecht, Martin; Puehler, Thomas; Cremer, Jochen; Berndt, Rouven
Abstract : Objective: To compare the percutaneous Rotarex and Angiojet thrombectomy devices with regard to effectiveness and in vitro safety. Methods: The Rotarex and Angiojet devices were evaluated in an established in vitro pulsatile flow model with a human femoropopliteal vessel phantom. First pass recanalisation and thrombus weight were assessed after thrombectomy, as well as micro- and macro-emboli. Further, histological evaluation of the vascular phantom was performed to analyse vascular injuries. Results: Thrombus weight did not differ significantly prior to the thrombectomy between the groups, but the Rotarex showed slight advantages in thrombus removal vs. the Angiojet regarding first pass recanalisation. Micro- and macro-emboli occurred in most of the endovascular manoeuvres performed; however, significantly more macro-emboli (2.37 ± 1.51 vs. 0.87 ± 0.83; p  = .048) were observed using the Rotarex than the Angiojet. Macroscopic dissections were detected in the Rotarex group ( n  = 3) but not in the Angiojet group. Microscopic vascular injuries were detected significantly more often in the Rotarex group (Rotarex: 531.61 μm ± 102.81 μm; Angiojet: 705.42 μm ± 61.68 μm [ p  = .001]). Conclusion: Both devices showed a comparable performance, with a slight advantage for the Rotarex regarding first pass recanalisation. Significantly more thrombo-emboli, and vascular injuries were observed in the Rotarex group with the latter being obviously the more tissue preserving procedure but potentially with a lower rate of recanalisation. Based on the present results, clinical randomised trials, including long term follow up, are needed to optimise and improve the use of catheter based procedures, taking into account the thrombus entity, localisation, and clinical history.